Prerequisites for sustainable life style changes among older persons with obesity and for ICT support - Axelsson, Sarianne Wiklund (Luleå tekniska universitet, Hälsa och rehabilitering, 2015)
The experiences from persons in the third age of lifestyle changes due to obesity are rarely described in research. Interventions regarding lifestyle changes and obesity show weak evidence for long-term effects. Information and communication technology (ICT) may add an important potential in interventions, but readiness among older persons and the actual needs for support must be explored. Therefore the overall aim for the thesis was to explore the prerequisites for sustainable lifestyle changes among older persons with obesity; and how this could be supported by ICT.Both qualitative and quantitative approaches were used. In paper I, 10 participants were individually interviewed about their experiences of lifestyle changes and in a multistage focus group study (paper IV), 6 participants expressed the support needed for sustainable lifestyle changes in relation to obesity. Qualitative content analysis was used. In a randomly selected population survey, 154 participants responded to an enquiry about general and health related ICT usage (paper II). They also rated scenarios for expected psychosocial impact on web based e-health services and mobile health applications (paper III).An integration of the results identified four main findings: The first finding, A never-ending process of vigilance and vulnerability, showed constant attempts of weight loss and pre-occupation on not to fail in an un-supportive environment. The second finding; Need for psychosocial support marked that the process of lifestyle changes was influenced by factors as sensibility to moods, social support and others’ attitudes. It was therefore essential for the persons to achieve emotional balance. The third finding, ICT as a possible support for adaptability, presented that older Swedes expected a positive psychosocial impact by ICT, especially in a future perspective. ICT was most valued in the domain of adaptability. The degree of usage of health related ICT, however, was low, although persons with overweight had more experience of this usage. Finally, the fourth finding; Reconstructions from weight to health expresses the needs of reconstructing focus towards health, rather than being pre-occupied with weight loss. Physical activity that was associated to joy and to have a functioning body, a body that would serve them as before, were motives to lose weight.In conclusion, this thesis illustrates that a lifestyle change due to obesity in third age is lined with vigilance not to fail and requires a great deal of endurance and effort. The potential of ICT to support lifestyle changes is likely to be substantiated by the positive expectations on ICT from a psychosocial impact perspective, especially in views of the future. Findings indicate a need for moving focus from weight towards health and to see opportunities, and that psychosocial support and enjoyable physical activity are important prerequisites for sustainable change. === Godkänd; 2015; 20150325 (sarwik); Nedanstående person kommer att disputera för avläggande av filosofie doktorsexamen, Namn: Sarianne Wiklund Axelsson Ämne: Fysioterapi / Physiotherapy Avhandling: Prerequisites for Sustainable Life Style Changes Among Older Persons with Obesity and for ICT Support Opponent: Docent Anncristine Fjellman-Wiklund Institutionen för samhällsmedicin och rehabilitering Umeå Universitet Ordförande: Universitetslektor Mai Lindström Institutionen för hälsovetenskap Luleå tekniska universitet Tid: Fredag den 8 maj 2015, kl. 10.00 Plats: D770, Luleå tekniska universitet